Establishing police station design improving the health and wellness of police personnel in Davao City - Ociones, Earl Jann E. (2018)
The well-being in the modern workplace is an increasing relevant and necessary consideration in planning. It has long been believed that a police work is correlated with a host of diseases, illness, and ailments. Stress and shift work are the two primary factors identified and been associated with most of the health issues police offices encounter. This research used the principles of workplace health and well-being, along with anthropometrics, physical comfort, space programming, and active design in order to propose an efficient workplace for the police personnel. This study employed a post occupancy evaluation to the 10 existing police stations in Davao City and documented the illnesses of the police personnel through their annual medical exam and their anthropometric data. Results show that these police stations failed on the spatial configuration, workers comfort, and sanitation. Police personnel showed that Diabetes Mellitus, Hypercholesterolemia, Obesity and Hypertension could be correlated with their physical and working environment and that their anthropometrics are within the standard measurement (lower range). Furthermore, the study also identified and proposed locations for the additional 21 stations to augment the acceptable proportion of police personnel to city population. The proposed police station incorporated a physical environment that enables the personnel to do activities that lessen health problems and at the same time provide comfort and proper sanitation. These was achieved through proper allocation of spaces and efficient programming.